Retrospective evaluation of serum/plasma iron, red blood cell distribution width, and nucleated red blood cells in dogs with acute trauma (2009–2015): 129 cases. Issue 5 (3rd September 2019) - Fish, Eric J.; Hansen, Sonya C.; Spangler, Elizabeth A.; Gaillard, Philippe R.; Fan, Shirley; Bacek, Lenore M.
Abstract: Objective: To compare the prognostic value of admission hematologic parameters serum/plasma iron, red blood cell distribution width (RDW), and nucleated red blood cells (nRBCs) in dogs presenting with acute traumatic injury. Design: Retrospective observational study (2009‐2015). Setting: University teaching hospital. Animals: One hundred and twenty‐nine clinical dogs presenting within 24 hours of acute traumatic injury. Interventions: None. Measurements and Main Results: One hundred and twenty‐nine dogs met the inclusion criteria and 109 (84.5%) survived, while 20 (15.5%) died or were euthanized in hospital. Patients with blunt force trauma comprised 79.8% of the patient population; dogs with penetrating trauma comprised 20.2% of cases. Hypoferremia occurred in all nonsurvivors, and the median serum/plasma iron concentration was significantly lower in nonsurvivors than survivors ( P = 0.028). Normal or increased serum/plasma iron had 100% specificity and 100% positive predictive value for survival. Red blood cell distribution width was not significantly different between groups ( P = 0.417). The presence of nRBCs was significantly associated with nonsurvival ( P = 0.030), although the absolute nRBC concentrations were not significantly different ( P = 0.070). A multiple logistic regression model found age, type of injury, presence of nRBCs, and serum/plasma iron to be independent predictors of survival with an area under the receiver operator characteristic curve of 0.813. Conclusions: The presence of nRBCs and low serum/plasma iron are associated with mortality in patients with acute trauma; however, red blood cell distribution width was not associated with survival. Absence of hypoferremia was highly associated with a favorable prognosis in this patient population. These parameters may warrant inclusion in trauma scoring systems.